Pengaruh Literasi Keuangan Dan Pemasaran Media Sosial Terhadap Pengambilan Keputusan Nasabah Pembiayaan Mikro di PT. Pegadaian CP Sepanjang Sidoarjo - Ali Arasyid Zain; Dwi Widyastuti; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
This study aims to determine the Influence of Financial Literacy and Social Media Marketing on Microfinance Customer Decision Making at PT. Pegadaian CP Sepanjang Sidoarjo, both partially and simultaneously. The population in this study were customers who applied for Microfinance Loans at PT. Pegadaian CP Sepanjang Sidoarjo, the research period was from January to July 2023, the sample technique was determined using Arikunto's opinion with a total of 92 people and the analysis method used was descriptive analysis method, multiple linear regression analysis, and hypothesis testing. The results of partial hypothesis testing (t-test) showed that Financial Literacy (X1) and Social Media Marketing (X2) had a positive and significant effect on Customer Decision Making, with a t-value of the Ease of Service variable of 3.384 while the t-table was 1.662 (t-count> from t-table). Meanwhile, for the social media marketing variable, the t-value was 2.924 while the t-table was 1.662 (t-count> t-table). The results of simultaneous hypothesis testing (F test) show that financial literacy (X1) and social media marketing (X2) have a positive and significant effect on customer decision making, with a calculated f value of 14.063 while ttable is 3.10 (Fcalculation is greater than Ftable). The results of the determination coefficient test (R2) show an Adjusted R square value of 0.223 or 22.3%, which indicates that financial literacy and social media marketing simultaneously contribute to customer decision making by 22.3%.